The Extent of Effectiveness of Balanced Scorecard in the Ministry of Education in the Sultanate of Oman - Alnabhani, Ahmed bin Sulaiman; Aljaraideh, Mohammed Sulaiman (Dirasat: Educational Sciences, 2021)
This study aims to identify the extent of effectiveness of balanced scorecard in the Ministry of Education in the Sultanate of Oman. To achieve the goal, the researcher designed a questionnaire that consisted of (23) items distributed in three areas. After confirming the indications of the questionnaire’s reliability and stability, it was distributed to (122) principals, assistants, department heads, and planning and follow-up members in the Ministry of Education. The study concluded that the degree of effectiveness of balanced scorecard came to a medium degree. The results also revealed that there were statistically significant differences attributed to job title in favor of the director of the department, while there were no statistically significant differences due to gender, educational qualification, and years of experience. The study recommends the necessity of providing electronic programs to support the application of balanced scorecard to increase the effectiveness of follow-up and evaluation, instilling a culture of managing strategic plans to raise awareness among employees, activating the participation of different administrative levels more in preparing and formulating the objectives of operational plans, and activating a system of administrative accountability.